Impact of the duration of farmland restoration on plant communities and soil carbon-nitrogen-phosphorus stoichiometry in the Southern Foothills of the Greater Khingan Mountains, Inner Mongolia - Yan Sheng; Fucang Qin; Yongjie Yue; Long Hai; Long Li; Xiaoyu Dong; Danlu Tao; Rong He; Kai Zhao (PLoS ONE, 2026)
The southern foothills of the Greater Khingan Mountains in Inner Mongolia are one of the 14 contiguous destitute areas in China. The ecological environment in the region is harsh. The implementation of the Grain-for-Green Project is crucial to the restoration and protection of local forest ecosystems. However, the project has some deficiencies in terms of plant communities and soil stoichiometric characteristics. In this study, the southern slope of Daxing’anling Forest in Inner Mongolia was used as the research area, and 1 year, 3 years, 5 years, 10 years, 20 years, abandoned land, and farmland after the restoration were comprehensively selected. The purpose of this study was to analyze the dynamic changes in soil stoichiometric characteristics and plant diversity during ecological restoration of this area, explore the influence of soil stoichiometric characteristics on plant diversity. The following results were obtained: (1) In terms of plant communities, plant species increased first and then decreased after returning farmland. In the early stage, pioneer herbs increased, and some species were eliminated due to competition and other factors in the later stage. Shrubs and trees appeared late, and herbs had strong adaptability. (2) In terms of soil stoichiometry, the contents of soil organic carbon (SOC) and total nitrogen (TN) were low in the early stage of returning farmland. With the increase in years, SOC increased first and then decreased, and TN increased. The changes in each soil layer were affected by many factors and differed from those of the control. The total phosphorus (TP) content fluctuated, and the ratios of C/N, C/P, and N/P had different trends in varying soil layers with returning farmland and vegetation restoration. (3) In terms of the relationship between vegetation and soil nutrients, SOC was positively correlated with TN, TN was positively correlated with the evenness index, and TP was negatively correlated with some vegetation indexes. This work has important guiding significance for improving soil fertility and plant growth in returning farmland to forest. This work is helpful to realize ecological environment protection and sustainable agricultural development.